Exploration in the world of the ancients - Bowman, John Stewart 1931- (Facts On File, 2005)
Discusses the voyages, navigation routes, and watercraft of explorers in the ancient world, from prehistoric times to the beginning of the Middle Ages.
Keywords: Geschichte; Geography, Ancient -- Juvenile literature; Discoveries in geography -- Juvenile literature; Geography, Ancient; Discoveries in geography; Explorers; Altertum; Entdeckungsreise